Towards next generation Internet of Energy system: Framework and trends - Muqit, Farhan (2023)
The quickening propensity of growth within the areas of information and communications technology and energy networks has triggered the emergence of a central idea termed as Internet of Energy (IoE). Such a concept relates the internet of things, which is the term used in describing the usage of sophisticated digital control devices with the capability of transmitting data via IT systems. The concept of an interconnected energy network is being formed in the upcoming days through upgrades in the field of intelligent energy systems to control real-time energy optimization and management. The energy industry has had a sustained expansion, reaching the IoE milestone and continuing to this cutting-edge power system, which is the next generation of IoE. A directional pathway from the traditional power system to the IoE has been conducted in this research work by addressing the importance of integrating the smart transmission and communication infrastructure, smart metering, pricing and energy management scheme. A detailed investigation of the IoE with respect to technical angles, such as communication architecture, IoE on the supply & demand side, and IoE protocol based on fundamental elements and essential technologies has been carried out to indicate the blueprint and jurisdiction complexity. The integration, security and energy management challenges may deviate the performance of the IoE technology that has been focused with proper control issues and solutions. Finally, a directional framework to establish the next-generation IoE system has been constructed with future scopes to insure higher resiliency, cyber-security and stability.